Wireless Pulmonary Artery Pressure Monitoring Guides Management to Reduce Decompensation in Heart Failure With Preserved Ejection Fraction - Adamson, Philip B.; Abraham, William T.; Bourge, Robert C.; Costanzo, Maria Rosa; Hasan, Ayesha; Yadav, Chethan; Henderson, John; Cowart, Pam; Stevenson, Lynne Warner (Circulation. Heart failure, 2014)
No treatment strategies have been demonstrated to be beneficial for the population for patients with heart failure (HF) and preserved ejection fraction (EF). The CardioMEMS Heart Sensor Allows Monitoring of Pressure to Improve Outcomes in NYHA Class III Heart Failure Patients (CHAMPION) trial was a prospective, single-blinded, randomized controlled clinical trial testing the hypothesis that hemodynamically guided HF management decreases decompensation leading to hospitalization. Of the 550 patients enrolled in the study, 119 had left ventricular EF ≥40% (average, 50.6%), 430 patients had low left ventricular EF (<40%; average, 23.3%), and 1 patient had no documented left ventricular EF. A microelectromechanical system pressure sensor was permanently implanted in all participants during right heart catheterization. After implant, subjects were randomly assigned in single-blind fashion to a treatment group in whom daily uploaded pressures were used in a treatment strategy for HF management or to a control group in whom standard HF management included weight-monitoring, and pressures were uploaded but not available for investigator use. The primary efficacy end point of HF hospitalization rate >6 months for preserved EF patients was 46% lower in the treatment group compared with control (incidence rate ratio, 0.54; 95% confidence interval, 0.38-0.70; P<0.0001). After an average of 17.6 months of blinded follow-up, the hospitalization rate was 50% lower (incidence rate ratio, 0.50; 95% confidence interval, 0.35-0.70; P<0.0001). In response to pulmonary artery pressure information, more changes in diuretic and vasodilator therapies were made in the treatment group. Hemodynamically guided management of patients with HF with preserved EF reduced decompensation leading to hospitalization compared with standard HF management strategies. http://www.clinicaltrials.gov. Unique identifier: NCT00531661.